1989
DOI: 10.1029/jd094id11p13207
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of cloud‐to‐ground lightning flash characteristics in the coastal area of the Sea of Japan

Abstract: Cloud‐to‐ground lightning flashes in a coastal area of the Sea of Japan have been observed for a few years by a magnetic direction‐finding system for lightning return strokes. Through the operational evaluation of the system, the data obtained so far have been carefully analyzed and corrected. In winter the activity of lightning does not move inland farther than 20–30 km from the coastline, and most of the flashes are detected on the sea. Seasonal variations are also found in polarities and magnetic signal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Over time, both the fraction and maximal magnitude of strong currents of both polarities increase. Similar trends have been observed over the east coast of the United States (Orville et al, 1987) and over the Sea of Japan (Hojo et al, 1989). The zoom-in window (Fig.…”
Section: Distributions Of Peak Currentssupporting
confidence: 63%
See 1 more Smart Citation
“…Over time, both the fraction and maximal magnitude of strong currents of both polarities increase. Similar trends have been observed over the east coast of the United States (Orville et al, 1987) and over the Sea of Japan (Hojo et al, 1989). The zoom-in window (Fig.…”
Section: Distributions Of Peak Currentssupporting
confidence: 63%
“…The fraction increases from 1.2 ± 1 % in early fall (FCL) to 17 ± 7 % in late winter (WCL). A higher fraction of positive strokes during winter storms was observed in previous studies over this region (Yair et al, 1998) and studies conducted worldwide (e.g., Hojo et al,1989;Ezcurra et al, 2002;Finke and Hauf, 1996).…”
Section: Fraction Of Positive Strokesmentioning
confidence: 62%
“…Also, we found that the percentage of +CG lightning (P (+)) for the observation areas close to the sea (8.6-11.9%) was higher than for those far from the sea (6.5-8.0%). Compared with the P (+) in Tibetan Plateau (16%) [Qie et al, 2002], Lanzhou (9.2%) [Qie et al, 1991], and Beijing (10.9%) [Zhang et al, 2010] in the northern part of China, or in the Japan sea coast in winter (50-60%) [Hojo et al, 1989], the P (+) in the PRD region was lower. The high percentage (>90%) of ÀCG lightning suggests that the thunderstorm cloud structure in the PRD region was dipolar (the top and bottom of the thunderstorm clouds were mainly of positive charge and negative charge).…”
Section: General Physical Properties Of Lightning In Prdmentioning
confidence: 99%
“…In 1995-97, the smallest percentage (6.5%) was observed in July 1995, and the largest (about 25%) in January 1996 (Orville and Huffines 1999). In the coastal area of the Sea of Japan, the percentage of positive flashes reached a maximum of 60% in December (Hojo et al 1989). In France, a maximum percentage of positive flashes of 44% was observed in February (Le Boulch and Plantier 1990).…”
mentioning
confidence: 99%